Optical interventions for myopia control - Logan, Nicola S.; Bullimore, Mark A. (Eye (London), 2024)
A range of optical interventions have been developed to slow the progression of myopia. This review summarizes key studies and their outcomes. Peer-reviewed, randomized controlled clinical trials of at least 18 months duration were identified. Randomized clinical trials were identified and summarised: 13 for spectacles, 5 for overnight orthokeratology, 5 for soft contact lenses, and 3 for orthokeratology combined with low concentration atropine. Overnight orthokeratology trials were the most consistent with 2-year slowing of axial elongation between 0.24 and 0.32 mm. Other modalities were more variable due to the wide range of optical designs. Among spectacle interventions, progressive addition lenses were the least effective, slowing axial elongation and myopia progression by no more than 0.11 mm and 0.31 D, respectively. In contrast, novel designs with peripheral lenslets slow 2-year elongation and progression by up to 0.35 mm and 0.80 D. Among soft contact lens interventions, medium add concentric bifocals slow 3-year elongation and progression by only 0.07 mm and 0.16 D, while a dual-focus design slows 3-year elongation and progression by 0.28 mm and 0.67 D. In summary, all three optical interventions have the potential to significantly slow myopia progression. Quality of vision is largely unaffected, and safety is satisfactory. Areas of uncertainty include the potential for post-treatment acceleration of progression and the benefit of adding atropine to optical interventions.